Identifying Javanese cultural norms and addressing politeness maxims in mitigating verbal sexual violence - Tur, Ajar Pradika Ananta; Sabrina, Arini (EduLite: Journal of English Education, Literature and Culture, 2024)
In 2023, Yogyakarta Province has documented 308 instances of sexual violence, including cases of verbal abuse. This fact is surprising given Yogyakarta's unique position as a cultural showcase in Indonesia, which is particularly evident in its depictions of politeness and identity. In contrast, Yogyakarta's Javanese propriety culture, known as unggah-ungguh, functions as a vital protective mechanism for its community by integrating local cultural components. This distinctive cultural politeness parallels Leech's Six Maxims of Politeness: Tact Maxim, Generosity Maxim, Approbation Maxim, Modesty Maxim, Agreement Maxim, and Sympathy Maxim. This research examines the correlation between these maxims and Javanese parenting practices as delineated in publications by the Department of Women's Empowerment, Child Protection, and Population Control of Yogyakarta, aimed at educators and parents in Yogyakarta, emphasizing the significance of courteous communication and virtuous conduct grounded in Javanese tradition. Strengthening the initiative from school to university levels, together with adequate support from family and community, may lead to a reduction in verbal sexual assault.